The fractions and burden of cardiovascular diseases and depression attributable to psychosocial work exposures in the European Union - Hélène Sultan Taïeb; Tania Villeneuve; Jean-François Chastang; Isabelle Niedhammer (European Trade Union Institute (ETUI), 2023)
This research project financed by the ETUI pursued two objectives: to estimate the fractions of cardiovascular disease and depression attributable to five different psychosocial work factors, i.e. job strain, effort-reward imbalance, job insecurity, long working hours, and bullying in Europe (35 countries, including 28 European Union countries), for each country and all countries taken together, in 2015; to estimate the annual burden of cardiovascular diseases and depression attributable to the five psychosocial work exposures in 28 European Union countries (EU28) in 2015, in terms of prevalent cases, deaths, years of life lost (YLLs), years of life lost due to disability (YLDs), and disability adjusted life years (DALYs). The attributable fractions (AFs) of depression were all significant in EU28: job strain (16%), job insecurity (9%), bullying (9%), and effort-reward imbalance (6%). The AFs of depression were higher than those of cardiovascular diseases (for all exposures except long working hours). The AFs of cardiovascular diseases (including coronary/ischemic heart diseases (CHD), stroke, atrial fibrillation, peripheral artery disease, venous thromboembolism) ranged from 1% to 11%. Most of the AFs were significantly different from zero, except for the job strain-stroke pair. Differences in the AFs were observed between countries for all exposure outcome pairs related to the outcome of depression and also to exposure to long working hours. Differences between genders were found for long working hours, with higher AFs observed among men than among women for all outcomes. Our study showed a high burden of CHD and depression attributable to the studied psychosocial work exposures in the EU28 in 2015, with a higher burden for depression.
Keywords: 330; Herzkrankheit; Psychische Krankheit; Arbeitsbedingungen; EU-Staaten